Therapeutic effects of Fc gamma RIV inhibition are mediated by selectively blocking immune complex-induced neutrophil activation in epidermolysis bullosa acquisita - Haeger, Swantje C.; Kridin, Khalaf; Pieper, Mario; Griewahn, Laura; Nimmerjahn, Falk; Zillikens, Detlef; König, Peter; Ludwig, Ralf J.; Hundt, Jennifer E. (Frontiers in Immunology, 2022)
Epidermolysis bullosa acquisita (EBA) is a subepidermal autoimmune bullous disease caused by autoantibodies targeting type VII collagen (COL7). It is characterized by inflammation and subepidermal blistering mainly through immune complex (IC)-mediated activation of neutrophils. In experimental EBA, binding of neutrophils to ICs in the skin and induction of clinical disease depends on the expression of the Fc gamma receptor (FcR) IV. As activating FcR mediate both neutrophil extravasation and activation, we used multiphoton imaging to obtain further insights into the mechanistic contribution of FcRIV in the pathogenesis of EBA. First, we demonstrated that blocking FcRIV function completely protects LysM-eGFP mice against induction of antibody transfer-induced EBA. To visualize the interactions of anti-COL7 IgG and neutrophils in vivo, fluorescently labeled anti-COL7 IgG was injected into LysM-eGFP mice. Multiphoton microscopy was sequentially performed over a period of 8 days. At all time points, we observed a significantly higher extravasation of neutrophils into the skin of mice treated with anti-FcRIV antibody compared to controls. However, the percentage of detected neutrophils localized to the target antigen along the dermal-epidermal junction was comparable between both groups. Additionally, reactive oxygen release and migration in vitro assay data demonstrate that FcRIV antibody treatment inhibits the activation, but not the migration, of neutrophils. Our findings underscore the importance of advanced in vivo imaging techniques to understand the complexity of IC-mediated neutrophil-dependent inflammation, and indicate that the therapeutic utility of FcRIV blockade is achieved through impairment of IC-mediated neutrophil activation.